2020
DOI: 10.3389/fcell.2020.00699
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Med23 Regulates Adult Hippocampal Neurogenesis

Abstract: Mammalian Mediator (Med) is a key regulator of gene expression by linking transcription factors to RNA polymerase II (Pol II) transcription machineries. The Mediator subunit 23 (Med23) is a member of the conserved Med protein complex and plays essential roles in diverse biological processes including adipogenesis, carcinogenesis, osteoblast differentiation, and T-cell activation. However, its potential functions in the nervous system remain unknown. We report here that Med23 is required for adult hippocampal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Another group of animals receive two labels separated by a time interval longer than the difference between the cell cycle length and the S-phase duration, and subsequent cell quantifications enable the calculation of the cell cycle length. This approach can be applied when we need to test whether any physiological or pathological stimulus alters the cell cycle parameters of a given population of proliferating cells ( 113 , 114 , 115 , 116 ).…”
Section: Labeling Schemes and Respective Readouts For Revealing Key Parameters Of Cell Cycle Kineticsmentioning
confidence: 99%
“…Another group of animals receive two labels separated by a time interval longer than the difference between the cell cycle length and the S-phase duration, and subsequent cell quantifications enable the calculation of the cell cycle length. This approach can be applied when we need to test whether any physiological or pathological stimulus alters the cell cycle parameters of a given population of proliferating cells ( 113 , 114 , 115 , 116 ).…”
Section: Labeling Schemes and Respective Readouts For Revealing Key Parameters Of Cell Cycle Kineticsmentioning
confidence: 99%
“…It is of relevance to note that deletion of individual MED subunits in B cell, T cell, and embryonic stem cells (ESC) revealed that only a fraction of genes was affected and that the number of differentially expressed genes was variable in different cell types, although the overall viability of cells was dramatically decreased [35]. Variation in the number of genes affected by MED subunit deletion has also been widely recognized in multiple other cell types, such as deletion of MED23 in mouse embryonic stem cells (ESCs) [47], mouse embryonic fibroblasts (MEFs) [48], mesenchymal stem cells [49], hematopoietic stem cells [50], adult hippocampal neural stem cells (NSCs) [51] and hepatocytes [52]. Another possible explanation for the large difference in the number of genes differentially expressed consequent to MED30 ablation in embryonic versus adult heart, is that, in embryonic heart, RNAseq was performed at E10.5, prior to onset of overt cardiac phenotypes, therefore likely excluding secondary gene changes.…”
Section: Discussionmentioning
confidence: 99%
“…The data were uploaded in the SRA database ( https://www.ncbi.nlm.nih.gov/sra ) as PRJNA792697 and PRJNA777369. The significant enrichment of Gene Ontology (GO) functional terms with overlapped genes that showed differential expression was analyzed, which covered the three domains of cellular component, molecular function, and biological process ( Chen et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%